On Weakly Pure Submodules of Locally Multiplication Modules - Jabbar, Adil Kadir; Hussein, Pery Karim (Sulaimani Journal for Pure and Applied Sciences, 2020)
In this paper, the definition of weakly pure submodule is introduced and studied and also weakly pure submodules of locally multiplication modules are studied and some properties that concern this type of modules in locally multiplication modules are proved. In addition, several properties of multiplication modules have been extended to locally multiplication modules and some relations that concerning weakly pure submodules and weakly pure submodules are obtained.
Keywords: Weakly pure submodules; multiplication modules; locally multiplication modules; faithful modules and weakly pure submodule